Dinamismo estrutural e transformação monocristal para monocristal de novas estruturas estendidas de chumbo(II) - Menezes, Bryan Brummelhaus de (2016)
The reaction of 1,4-α,α’-xylenediylbis(phenylphosphinic acid) (H2XBPP) with lead(II) generated two different extended structures: [Pb3(XBPP)3(H2O)] 1 and [Pb5(μ3-O)(XBPP)4(H2O)] 5 depending on the pH employed in the reaction. The difference be-tween the structures of 1 and 5 is the presence of a μ3-oxo bridge between three lead atoms. Through post synthetic structure modifications of 1, four new compounds with extended structures were synthesized. Three of these – [Pb4(XBPP)4(H2O)] 2, [Pb(XBPP)] 3 and [Pb2(XBPP)2(H2O)] 4 – are pseudo-polymorphs obtained by a re-versible dehydration/rehydration process. These transformations were observed in the polycrystalline powder as well as in single crystal. The hydrothermal reaction of 1 at pH 2 gave [Pb(HXBPP)2] 7. One pseudo-polymorph, [Pb5(μ3-O)(XBPP)4] 6, was ob-tained from the dehydration of 5. Six structures, 1 – 6, showed a very similar three-dimensional arrangement with the same pcu topology. Compound 7 had a two-dimen-sional extended structure with sql planar topology. The compounds synthesized in this work were characterized by elemental analysis, infrared and Raman spectroscopy, powder and single crystal X ray diffraction, thermogravimetric analysis and 31P solid state nuclear magnetic resonance. A kinetic study of the water loss and water uptake reactions, DFT calculations, and a gas adsorption study with N2, CO2 and water vapor were performed.